Are banks really special? New evidence from the FDIC-induced failure of healthy banks - Adam B. Ashcraft (Federal Reserve Bank of New York, 2003)
The FDIC used cross-guarantees to close thirty-eight subsidiaries of First RepublicBank Corporation in 1988 and eighteen subsidiaries of First City Bancorporation in 1992 when lead banks from each of these Texas-based bank holding companies were declared insolvent. I use this exogenous failure of otherwise healthy subsidiary banks as a natural experiment for studying the impact of bank failure on local-area real economic activity. I find that the closings of the subsidiaries were associated with a significant decline in bank lending that led to a permanent reduction in real county income of about 3 percent.
Keywords: E5; G18; G33; 330; bank failures; cross-guarantee; uniqueness of banks; Bankenpolitik; Bankinsolvenz; Einlagensicherung; USA